Click Synthesis and Biologic Evaluation of ()- and ()-2-Amino-3-[1-(2-[F]Fluoroethyl)-1-[1,2,3]Triazol-4-yl]Propanoic Acid for Brain Tumor Imaging with Positron Emission Tomography - Jonathan McConathy; Dong Zhou; Stephany E. Shockley; Lynne A. Jones; Elizabeth A. Griffin; Hsiaoju Lee; Susan J. Adams; Robert H. Mach (Molecular Imaging)
The ( R )- and ( S )-enantiomers of 2-amino-3-[1-(2-[ 18 F]fluoroethyl)-1 H -[1,2,3]triazol-4-yl]propanoic acid (4) were synthesized and evaluated in the rat 9L gliosarcoma brain tumor model using cell uptake assays, biodistribution studies, and micro-positron emission tomography (microPET). The ( R )- and ( S )-enantiomers of [ 18 F]4 were radiolabeled separately using the click reaction in 57% and 51% decay-corrected yields, respectively. ( S )-[ 18 F]4 was a substrate for cationic amino acid transport and, to a lesser extent, system L transport in vitro. In vivo biodistribution studies demonstrated that ( S )-[ 18 F]4 provided higher tumor uptake and higher tumor to brain ratios (15:1 at the 30- and 60-minute time points) compared to the ( R )-enantiomer (7:1 at the 30- and 60-minute time points). MicroPET studies with ( S )-[ 18 F]4 confirmed that this tracer provides good target to background ratios for both subcutaneous and intracranial 9L gliosarcoma tumors. Based on these results, the 1 H -[1,2,3]triazole-substituted amino acid ( S )-[ 18 F]4 has promising PET properties for brain tumors and represents a novel class of radiolabeled amino acids for tumor imaging.